Clinical results in phacoemulsification using the SRK/T formula - Lagrasta,Juliana Marques de Souza (2009)
PURPOSE: To evaluate the prediction of refraction using the SRK/T formula for intraocular lens (IOL) calculation in eyes with medium axial length after phacoemulsification. METHODS: This prospective study enrolled 33 eyes with nuclear cataract that underwent phacoemulsification. All procedures were performed by one surgeon with the intraocular lens placed within the capsular bag. The same technician who was unaware of the purpose of the study made all the measurements. The achieved refractive error one month after surgery was compared to the predicted postoperative refractive error by the SRK/T formula. RESULTS: The ocular axial length varied between 22.2 mm and 24.5 mm. The mean predicted refraction was -0.431 ± 0.181 D and the mean achieved postoperative spherical equivalent was -0.220 ± 0.732 D. Eighteen eyes (55%) had a refractive error between ± 0.50 D and thirty eyes (91%) between ± 1.00 D of the predicted refraction. There was a tendency toward hyperopic shift (mean ± SD: 0.211 ± 0.708 D, p=0.009). CONCLUSION: The SRK/T formula demonstrated a satisfactory accuracy to calculate the error of refraction in eyes with medium axial length.